2023
DOI: 10.1080/17482631.2023.2184034
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical experiences of healthcare workers during COVID-19: a qualitative analysis of anonymous, web-based, audio narratives

Abstract: Purpose To gain a deeper understanding of healthcare workers experiences during COVID-19 using an anonymous, web-based, audio narrative platform. Methods Data were collected from healthcare workers in the midwestern United States using a web-enabled audio diary approach. Participant recordings were analysed using a narrative coding and conceptualization process derived from grounded theory coding techniques. Results Fifteen healthcare workers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…caring for patients with COVID-19, special attention was paid to the risk of burnout and compassion fatigue and to the need to both build resilience among professionals [45,46] and mitigate the repeated trauma exposure [47]. In our study, we also found experiences connected to the interpersonal world (focus: belonging).…”
Section: Original Articlementioning
confidence: 63%
See 1 more Smart Citation
“…caring for patients with COVID-19, special attention was paid to the risk of burnout and compassion fatigue and to the need to both build resilience among professionals [45,46] and mitigate the repeated trauma exposure [47]. In our study, we also found experiences connected to the interpersonal world (focus: belonging).…”
Section: Original Articlementioning
confidence: 63%
“…An important contribution of this study relies on the fact that data consisted of (almost) "naturally-occurring narratives", and were not framed by investigators' questions, thus revealing matters of interest, satisfaction and concern of physicians during W1. A similar approach was adopted by Lackman-Zeman et al, [46] who used web-enabled audio diaries.…”
Section: Original Articlementioning
confidence: 99%
“…While the frst two themes appeared in the previous analysis during the frst wave of the pandemic [5], the themes of leadership failures and changing roles emerged during the second surge of the pandemic. Tough many studies also reported similar fndings related to the frst two themes, relatively few studies have highlighted leadership issues and changing role expectations during the pandemic [9,10].…”
Section: Discussionmentioning
confidence: 89%
“…Comparing the frst and second audio diary analyses from the larger study ofered the following insights [5]: First, there was a continuation of stories relating to both fear and hope. Te frst analysis labeled the themes as paradoxical.…”
Section: Discussionmentioning
confidence: 98%